Action of Trypsin on Amidinated Fibrinogen - Phillips, H. M; York, J Lyndal (Thrombosis and Haemostasis, 1974)
A study of the action of trypsin on fibrinogen with lysine side chains chemically blocked by amidination was undertaken to determine whether trypsin attacks arginine or lysine linkages in fibrinogen in order to render it nonclottable. The data suggests that trypsin attacks arginine site(s).